A teoria da consciência de Searle e sua crítica ao cognitivismo - Lima, Silmara Natifate da Silva (2023)
In The Rediscovery of the Mind, the American philosopher John Searle presented to the world his general theory of the mind, which had as its central proposal to make qualitative and subjective specifications central themes in discussions about the mind, giving them a naturalistic approach in contrast to the dualist approach that he saw in most contemporary theories. The aims of the author's theory also included: overcoming traditional theories in the study of the mind (more specifically, dualism and materialism); demonstrate that consciousness is the most fundamental characteristics of minds; and refutes Computationalism, in particular, the aspect he called “Cognitivism”. This work is about the last two claims, that is, to present the Searlean hypothesis that consciousness is central and fundamental to characterize the mind, and to contemplate, from this, the reasons why the author disapproves of computationalist ideas and rejects cognitivism. Finally, we must reflect on whether his hypotheses regarding the centrality of consciousness are supported and whether his criticisms of cognitivism are justified.